Adsorption behaviors and mechanisms of Cu2+, Zn2+ and Pb2+ by magnetically modified lignite - Junzhen Di; Zhen Ruan; Siyi Zhang; Yanrong Dong; Saiou Fu; Hanzhe Li; Guoliang Jiang (Scientific Reports, 2022)
Abstract The study aims to solve the problems of limited capacity and difficult recovery of lignite to adsort Cu2+, Zn2+ and Pb2+ in acid mine wastewater (AMD). Magnetically modified lignite (MML) was prepared by the chemical co-precipitation method. Static beaker experiments and dynamic continuous column experiments were set up to explore the adsorption properties of Cu2+, Zn2+ and Pb2+ by lignite and MML. Lignite and MML before and after the adsorption of heavy metal ions were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectrometer (FTIR). Meanwhile, the adsorption mechanisms of Cu2+, Zn2+ and Pb2+ by lignite and MML were revealed by combining the adsorption isotherm model and the adsorption kinetics model. The results showed that the pH, adsorbent dosage, temperature, initial concentration of heavy metal ions, and contact time had an influence on the adsorption of Cu2+, Zn2+ and Pb2+ by lignite and MML, and the adsorption processes were more in line with the Langmuir model. The adsorption kinetics experiments showed that the adsorption processes were jointly controlled by multiple adsorption stages. The adsorption of heavy metal ions by lignite obeyed the Quasi first-order kinetic model, while the adsorption of MML was chemisorption that obeyed the Quasi second-order kinetic model. The negative ΔG and positive ΔH of Cu2+ and Zn2+ indicated the spontaneous and endothermic nature reaction, while the negative ΔH of Pb2+ indicated the exothermic nature reaction. The dynamic continuous column experiments showed that the average removal rates of Cu2+, Zn2+ and Pb2+ by lignite were 78.00, 76.97 and 78.65%, respectively, and those of heavy metal ions by MML were 82.83, 81.57 and 83.50%, respectively. Compared with lignite, the adsorption effect of MML was better. As shown by SEM, XRD and FTIR tests, Fe3O4 was successfully loaded on the surface of lignite during the magnetic modification, which made the surface morphology of lignite coarser. Lignite and MML removed Cu2+, Zn2+ and Pb2+ from AMD in different forms. In addition, the adsorption process of MML is related to the O–H stretching vibration of carboxylic acid ions and the Fe–O stretching vibration of Fe3O4 particles.